Potential of Endophytic Yeast Candida sanyaensis and Candida sp. from Nira Siwalan (Borassus flabellifer L.) as a Bread Dough Leavening Agent - Putri Dwi Avitasari; Ulfah Utami; Liliek Harianie (Jurnal Biodjati, 2026)
The increasing global demand for bread has driven the bakery industry to seek alternative leavening agents to reduce dependence on commercial yeast imports. Endophytic yeasts isolated from local agricultural sources offer promising potential for sustainable bread production. This study aimed to evaluate the potential of endophytic yeast isolates Candida sanyaensis and Candida sp., previously isolated from Nira Siwalan (Borassus flabellifer L.), as bread dough leavening agents. The research assessed the tolerance of both yeast isolates to various temperatures (30°C, 37°C, and 45°C) and ethanol concentrations (10%, 13%, and 15%) by measuring optical density using UV-Vis spectrophotometry at 24 and 72 hours of incubation. Additionally, the quality of bread fermented by these isolates was evaluated through texture profile analysis (hardness, cohesiveness, adhesiveness, and gumminess) and color analysis (L, a, b* values) using a texture analyzer and color reader, respectively. Commercial instant yeast (Saccharomyces cerevisiae) served as a positive control, while dough without yeast served as a negative control. The results demonstrated that both Candida sanyaensis and Candida sp. were tolerant to high temperature (45°C) and high ethanol concentration (15%), as indicated by increased cell density from 24 to 72 hours of incubation. Bread fermented with both endophytic yeast isolates exhibited texture and color characteristics similar to those of bread fermented with commercial yeast, with a soft texture and a light brown color. Statistical analysis using ANOVA and DMRT at the 5% significance level revealed no significant differences in texture and color parameters between bread produced with the endophytic yeast isolates and the commercial yeast control. These findings suggest that Candida sanyaensis and Candida sp. isolated from Nira Siwalan (Borassus flabellifer L.) possess promising potential as alternative bread dough leavening agents, offering a sustainable approach to reducing dependency on imported commercial yeast in the bakery industry.